Mature cystic teratoma mimicking ectopic pregnancy: a case report - Verma, Deepak; Kumar, Sumit; Sachdev, Namrita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
We present a case of mature cystic teratoma resembling ectopic pregnancy in a patient with positive serum beta-hCG and an adnexal mass. A 30-year-old woman who was experiencing pelvic pain and vaginal bleeding was sent to the emergency room. An ultrasound revealed a complex right adnexal mass measuring 63×42 mm and the absence of an intrauterine gestational sac. Based on these findings, ectopic pregnancy was suspected; nevertheless, a subsequent magnetic resonance imaging (MRI) was planned, which suggested mature cystic teratoma. On a laparoscopy, later findings were verified. Cyst removal was the patient’s treatment. Despite the possibility of an ectopic pregnancy being indicated by the existence of an adnexal mass without an intrauterine gestational sac and a positive beta-hCG level, a mature cystic teratoma should be considered as a differential diagnosis.